2017
DOI: 10.1080/10408398.2016.1220915
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and its impact on maternal-fetal outcomes in pregnancy: A critical review

Abstract: The role of vitamin D beyond its classical function in calcium homeostasis has been of significant interest in recent years. There has been expanding research on the pleiotropic role of vitamin D in pregnancy and the implications of its deficiency on maternal-fetal outcomes. Several studies have associated low maternal vitamin D status to adverse outcomes in pregnancy, including preeclampsia, gestational diabetes, preterm births, low birth weight, and others. Several randomized controlled clinical trials of Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 101 publications
(155 reference statements)
1
110
0
3
Order By: Relevance
“…Systematic reviews and meta-analysis, including cross-sectional, longitudinal, cohort, ecological, and observational studies, indicate inconsistent results regarding the association between vitamin D deficiency and PET. Some studies reported an increased risk of PET women with vitamin D deficiency in pregnancy in contrast with others [43][44][45]. This contradiction of finding can be explained by different vitamin D assessment methods, criteria applied to define vitamin D deficiency, different season and trimester in studies [44].…”
Section: Gestational Hypertension and Preeclampsiamentioning
confidence: 95%
See 3 more Smart Citations
“…Systematic reviews and meta-analysis, including cross-sectional, longitudinal, cohort, ecological, and observational studies, indicate inconsistent results regarding the association between vitamin D deficiency and PET. Some studies reported an increased risk of PET women with vitamin D deficiency in pregnancy in contrast with others [43][44][45]. This contradiction of finding can be explained by different vitamin D assessment methods, criteria applied to define vitamin D deficiency, different season and trimester in studies [44].…”
Section: Gestational Hypertension and Preeclampsiamentioning
confidence: 95%
“…Moreover, the immune cell regulation role of vitamin D protects β-cells from damaging and improves its function [50,51]. Although vitamin D deficiency can be associated with the pathogenesis of diabetes mellitus type 1 and type 2, its role in GDM is not conclusive [43]. Conflicting results have been found in case-control, prospective cohort studies, and reviews looking into the risk of GDM with vitamin D status [46].…”
Section: Gestational Diabetes Mellitus (Gdm)mentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these are gestational diabetes mellitus and preeclampsia in mother (Abedi, Mohaghegh, Afshary, & Latifi, 2014), small for gestational age (SGA), low birth weight, and respiratory problems like wheezing and asthma in child (Newhook et al, 2009). Of the adverse birth outcomes associated with vitamin D deficiency (VDD), preterm delivery, abortion, and caesarean section can be mentioned (Agarwal, Kovilam, & Agrawal, 2018;Wei, 2014).…”
Section: Introductionmentioning
confidence: 99%